Ambivalenz der Wiedereingliederung Betriebliche und sozialstaatliche Integrationsmassnahmen aus der Sicht gesundheitlich beeinträchtigter Personen - Hassler, Benedikt (Studies on the Social Question, 2021)
"Employers and insurances in Switzerland have introduced new instruments to support the return to work process of sick workers. A key instrument in this regard has been the introduction of case managers in companies. But what are the consequences of these measures on the "selves" of the supported employees? The grounded theory study answers this question based on 16 interviews with employees who have successfully returned to work after serious sickness or accident. The results show that employees are reluctant to accept case management support. Establishing a sustainable relationship between case management and supported employees takes time, but eventually is successful due to a moral division of labour (Hughes) within the companies. The disability insurance is viewed as a potential danger to one's self, because the insurance is associated with labels such as disability, dependency or fraud. In the return to work process, primary and secondary adjustments (Goffman) to organisational expectations play an essential role. Employees must demonstrate a strong will to return to work and they feel compelled to accept all adaptations made by the company in order to keep the job. However, these primary adjustments lead to cognitive dissonance among the affected individuals. Secondary adjustments, such as reduced identification with the job or the employer, allow to reduce these tensions. "